Perlindungan Hukum Terhadap Pemilik Hak Atas Tanah Dalam Proses Pengadaan Tanah Untuk Kepentingan Umum - Dwi Nurul Aulia Pattiha; Jemmy Jefry Pietersz; Novyta Uktolseja (PATTIMURA Law Study Review, 2023)
ABSTRACT: Procurement of land for public purposes is not carried out according to the stages such as planning, preparation, implementation and delivery of results and even at these 4 (four) stages disputes often occur so that owners of land rights lose their rights without compensation or the compensation they receive is not appropriate as a form of legal protection for the owner of the right to land. Purposes of the Research, reviewing and analyzing the land acquisition process for public interest can lead to land acquisition disputes, as well as reviewing and analyzing legal remedies for owners of land rights in the process of land acquisition for public interests. Methods of the Research the type of research used is normative juridical research using a problem approach, namely the statutory approach and the concept approach. While the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Legal material collection techniques through library research with legal material analysis techniques, namely qualitative. Research results show that land acquisition for the public interest is very prone to causing disputes. This is because in the process of land acquisition for the public interest it is not carried out based on the provisions, because land acquisition for development for the public interest is carried out through the stages of: planning, preparation, implementation and delivery of results, not implemented These four stages cause disputes in the process of land acquisition for the public interest so that owners of land rights can take legal action as a form of legal protection against ownership of land rights to obtain compensation or objections can be made through non-litigation channels, namely deliberations, while the litigation path, namely the judicial process of Objections to location determination can be submitted to the PTUN, while objections to determining the form and amount of compensation are submitted to the local District Court.